Advances in complex geometry - Rubinstein, Yanir A.; Shiffman, Bernard (Contemporary mathematics (American Mathematical Society), 2019)
This volume contains contributions from speakers at the 2015-2018 joint Johns Hopkins University and University of Maryland Complex Geometry Seminar. It begins with a survey article on recent developments in pluripotential theory and its applications to Kähler-Einstein metrics and continues with articles devoted to various aspects of the theory of complex manifolds and functions on such manifolds.